Instrumentasi Pemeriksaan Sanitasi Pada Pembuatan Jamu Skala Industri Rumah Tangga - Naila Firka Nida; Mohamad Mirza Fauzie; Siti Hani Istiqomah (Sanitasi: Jurnal Kesehatan Lingkungan, 2022)
A research instrument is a research tools used to collect, examine, investigate a problem, and present data more systematically and objectively. ‘’Jamu gendong’’ is a traditional liquid medicine that is not preserved. The production process of herbal medicine must meet the Good Traditional Medicine Manufacturing Method (CPOTB) to protect the public against adverse things from the use of sling herbs that do not meet quality requirements. The purpose of this research is to create hygiene and sanitation examination instruments in the manufacture of herbal medicine in a household-scale industry. The design of this research is using 4 D models consisting of 4 main stages, namely: define, design, develop and disseminate. This method is used because it has the purpose of producing instruments in the form of questionnaires from the media. The developed instrument is then tested for feasibility with an expert validity test in public health center Jetis II Bantul by four validators and continued with instrument trials in Jamu Gendong Kiringan Tourism Village, Canden, Jetis, Bantul Regency. The test of the instrument was conducted by two surveyors of four industries or herbalists to find out how decent the quality of the instruments made by researchers for use by others. The results of this study showed that in expert validation tests instruments made by researchers are worth using for trials. As for the instrument trial activities conducted by surveyors showed that instruments made by researchers are worth using by others.